Viscoelastic Properties of Asphalts Based on Penetration and Softening Point - Radovskiy, Boris (Structural Integrity,, 2018)
This work deals with conventional and new relationships between various viscoelastic properties of road bitumen, determined under different test modes, such as constant stress, constant deformation or cyclic load. Approximate formulas have been derived for prediction of the rheological properties of asphalt based on its standard parameters such as penetration and softening point. The work is intended for researchers and engineers in road paving industry. It may be also of interest for teachers and Civil Engineering students.